Socio-economic imperatives of forest based rural livelihoods in climate constrained environments in Ondo State, Nigeria (2016)
The rural people have been recognized as knowledge holders on climate change. This work examines the socio-economic imperatives of such knowledge particularly as it affects livelihood in selected forest fringe communities in Ondo State, Nigeria. Multistage random sampling technique was adopted in which 4 Local Government Areas (LGAS): Odigbo, Akure North, Owo and Idanre were randomly selected in Ondo state. In each of the LGAs, a forest reserve (Oluwa, Ala, Owo and Idanre, respectively) was selected. Three rural communities surrounding each of the forest reserves were then selected while thirty respondents were randomly selected for interviews in each of the selected communities with the use of well-structured questionnaire. The data were analysed using descriptive and inferential statistics. More males (52.9%) were interviewed with majority (95.6%) being married while modal age group (42.2%) was between 30 and 40 years. A high percentage of the respondents (30.8%) had no formal education while 34.7% had only primary school leaving certificates. The modal household size was between 11 and 15 people in Owo LGA. Farming was the major source of livelihood for all the respondents. Most of the respondents (52.6%) were aware of climate change through radio. The source of their awareness was however, discovered to be a function of location, age, level of education and secondary occupation. Sources of awareness were found to be dependent upon respondents’ LGA (χ2 = 30.2, df = 12, p = 0.003), age (χ2 = 41.6, df = 8, p = 0.000), level of education (χ2 = 31.2, df = 16, p = 0.103) and secondary occupation (χ2 = 69.2, df = 44, p = 0.009). The dependence of respondents’ livelihoods on forest resources in this study is dependent on their LGA (χ2 = 25.0, df = 4, p = 0.000), age (χ2 = 34.6, df = 10, p = 0.001), years of resident (χ2 = 46.6, df = 12, p = 0.010) as well as their primary (χ2 = 64.5, df = 12, p = 0.000) and secondary (χ2 = 32.9, df = 7, p = 0.000) occupations. The annual income of respondents’ from their primary sources of livelihoods is dependent on their LGA (χ2 = 29.8, df = 12, p = 0.003), sex (χ2 = 23.0, df = 8, p = 0.003), Age (χ2 = 86.5, df = 16, p = 0.000), level of education (χ2 = 70.5, df = 16, p = 0.000), marital status (χ2 = 79.9, df = 8, p = 0.000) and primary occupation (χ2 = 363.9, df = 40, p = 0.000). The study established interdependence among respondents’ livelihoods, their socio-economic background, forest resources in the study area and climate. However, such dependency is location specific. It further observed climate change as negatively affecting agriculture and by extension food production in the study area. Creation of awareness for sustainable use of forest resources among residents and the identified alternative livelihoods to farming in Ondo State were recommended.